Ypsilandrosides U-Y, five new steroidal saponins from Ypsilandra thibetica - Wen-Tao Gao; Ling-Ling Yu; Jing Xie; Long-Gao Xiao; Shi-Juan Zhang; Wen-Yi Ma; Huan Yan; Hai-Yang Liu (Natural Products and Bioprospecting, 2022)
Abstract Phytochemical reinvestigation on the whole plants of Ypsilandra thibetica obtained four new spirostanol glycosides, named ypsilandrosides U-X (1–4), and one new cholestanol glycoside, named ypsilandroside Y (5). Their structures have been established by extensive spectroscopic data and chemical methods. Among them, compound 4 is a rare spirostanol glycoside which possesses a novel 5(6 → 7) abeo-steroidal aglycone, while compound 1 is a first spirostanol bisdesmoside attached to C-3 and C-12, respectively, isolated from the genus Ypsilandra. The induced platelet aggregation activity of the isolates was tested. Graphical Abstract